Infographic. COFIT-19: let`s get moving through the COVID-19 pandemic! - Fitzpatrick, J.; Castricum, A.; Seward, H.; Tulloh, L.; Dawson, E. (British Journal of Sports Medicine, 2020)
Are my unfit patients more at risk from COVID-19?